2022
DOI: 10.12659/ajcr.937517
|View full text |Cite
|
Sign up to set email alerts
|

A 60-Year-Old Man with Gingivitis and Poorly Controlled Diabetes Developing Low Back Pain 1 Week Following Recovery from COVID-19 Diagnosed with Spinal Abscess Due to Streptococcus oralis

Abstract: Patient: Male, 60-year-old Final Diagnosis: Pyogenic spinal infection Symptoms: Low back pain • neck pain Medication: — Clinical Procedure: Fine needle biopsy • magnetic resonance imaging Specialty: Infectious Diseases • Rehabilitation Objective: Rare disease Background: Streptococcus oralis ( S. oralis ) is a gram-positive bacterium and component of the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Choudhury et al [18] reported a patient with recurrent and persistent MSSA bacteremia and osteomyelitis, complicated by a spinal epidural abscess, bioprosthetic valve endocarditis, and aortic root abscess despite antibiotic treatment while having tested positive for SARS-CoV-2 infection, implying a COVID-19-induced immunocompromised state with functional exhaustion of CD4 and CD8 T-cells as the potential underlying mechanism for the persistence of such infections. In a report by Chu et al [19], a 60-yearold patient with diabetes and gingivitis developed Streptococcus oralis spinal infection with paraspinal, psoas, and epidural abscesses one week after recovery from a mild COVID-19 infection. The patient had not received any immunosuppressive treatment but did have risk factors for spinal infection-gingivitis and diabetes-similar to the case presented in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Choudhury et al [18] reported a patient with recurrent and persistent MSSA bacteremia and osteomyelitis, complicated by a spinal epidural abscess, bioprosthetic valve endocarditis, and aortic root abscess despite antibiotic treatment while having tested positive for SARS-CoV-2 infection, implying a COVID-19-induced immunocompromised state with functional exhaustion of CD4 and CD8 T-cells as the potential underlying mechanism for the persistence of such infections. In a report by Chu et al [19], a 60-yearold patient with diabetes and gingivitis developed Streptococcus oralis spinal infection with paraspinal, psoas, and epidural abscesses one week after recovery from a mild COVID-19 infection. The patient had not received any immunosuppressive treatment but did have risk factors for spinal infection-gingivitis and diabetes-similar to the case presented in this report.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides an important example of how challenging it can be to recognize an underlying infection in a patient with initial presentation of ankle pain. Although non-musculoskeletal conditions are rarely observed in chiropractic centers, cases involving infection and cardiovascular emergencies have been reported in the literature [ 19 , 20 ]. In the present case, a 71-year-old man with ankle pain was referred to a chiropractor who advised an MRI scan that revealed bilateral cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important aspect of chiropractic practice involves the diagnosis of neurological [14,15], gastrointestinal [16][17][18], and reproductive dysfunctions [19,20]. Additionally, considering the possibility of inflammatory arthritis [21,22], infections [23,24], cardiovascular diseases [25][26][27], systematic disorders [28], fractures [28,29], tendon ruptures [29,30], and metastatic conditions [31,32] that masquerade as musculoskeletal disorders is crucial for providing chiropractic care. Therefore, having access to laboratory testing and radiological imaging is vital for chiropractors to conduct comprehensive examinations, ruling out any underlying severe pathologies and ultimately enhancing the quality of life for their patients [33].…”
Section: Discussionmentioning
confidence: 99%